Penerapan Model Problem Based Learning untuk Meningkatkan Kemampuan Membuat Teks Prosedur pada Siswa Kelas VII SMPN 1 Warungkondang Cianjur (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study is motivated by the low ability of seventh-grade students to understand and write procedural texts, particularly in terms of linguistic features and the logical sequencing of steps. These conditions indicate the need for a learning model that actively engages students and enhances their analytical thinking skills. This research aims to examine the effect of the Problem Based Learning model on students’ ability to analyze and write procedural texts at SMP Negeri 1 Warungkondang. The study employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group. The research population consisted of all seventh-grade students, with a sample of 32 students divided into an experimental class and a control class. Data were collected through comprehension tests, procedural text writing assessments, and classroom observations of student learning activities. Statistical analysis was conducted to identify differences and improvements in students’ abilities following the implementation of the learning model. The findings reveal that students’ understanding of procedural text structure was at a moderate level, with the highest achievement in identifying text goals and the lowest in mastering linguistic features. Students’ writing ability was predominantly categorized as moderate, indicating that while they understood the basic structure of procedural texts, they encountered difficulties in organizing steps logically and in detail. Furthermore, the use of audiovisual media within problem-based learning significantly increased student engagement and learning enthusiasm, although oral communication skills remained limited. These results suggest that Problem Based Learning is effective in improving procedural text learning outcomes; however, it should be supported by focused linguistic guidance and staged writing practice to optimize students’ overall writing performance.